Controvérsias monetárias no Brasil imperial e suas influências na formação do pensamento desenvolvimentista brasileiro - Ivan Colangelo Salomão (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
During the nineteenth century, the Brazilian monetary debate involved the main leaders of the imperial bureaucracy, as well as congressmen and intellectuals. Opposing bullionists and anti-bullionists, the national debate was strongly influenced by the political reality observed in England. The relevance of anti-bullionism to the origins of Brazilian “developmentalist” thought shows the “tropicalisation” of economic ideas imported from Europe. Thus, this paper aims to analyze the mains issues of this debate, as well as the relevance of the anti-bullionists ideas and policies for the formation of “national developmentalism”.